Strategy for Developing the Quality of Human Resources (HR) of the Indonesian National Army (TNI) Through Strengthening Literacy Digital - Antoni, Hendro; Yanthy Yosepha, Sri (Dinasti International Journal of Digital Business Management, 2025)
The development of increasingly sophisticated technology has put the world in an era of increasingly complex international competition in various ways. This shift in life challenges requires the quality of human resources to be accompanied by quality. To balance this, human resources need to improve their digital literacy in order to be able to sort out information so as not to be trapped in a propaganda. However, in Indonesia the issue of literacy is still in the low category. When the government through Kominfo has made many improvements starting from conducting digital literacy counseling for all aspects, one of which is the TNI, as the party responsible for the stability and security of the country, digital literacy is very important for all aspects, especially the TNI, to be able to protect the community from various negative things. This research activity uses a type of qualitative research with a literature study method with the aim of analyzing the implementation of Digital Literacy as human resource development. The results of this study explain that the strategy of developing human resources through strengthening digital literacy in TNi can be done through digital literacy counseling, building digital crime skills, increasing digital literacy skills and digital transformation development capabilities.